Chile: Review of DIPRES' programme evaluation system - Beazley, Ivor (OECD Publishing, 2021)
This review analyses the institutional arrangements, evaluation instruments and processes involved in the evaluation of spending programmes and institutions in Chile. In particular, it examines the extent to which the Chilean Budget Office's ex post evaluations are used to inform budget decision making, as well as the wider relevance and use of evidence generated by these evaluations